La plaza del teatro como espacio de expresión artística en el centro de Quito - Fernández Solórzano, Andrés Leandro (2014)
Video Documentary: " La Plaza del Teatro como espacio de expresión artística en el Centro de Quito " showcases the work of popular artists in this public space and social relationships that develop between artist and viewer. The documentary contains testimonials from popular artists it is their job, their coexistence with the public opinion to the problems facing society, their perspective of what popular culture and belong to it. The testimony of university teachers what is the alternative communication micromedia, public spaces, street performers, and popular culture. In the theoretical concepts are supported above all on the part of the documentary.